Retrospective analysis of non-contact ACL injury risk: A case series review of elite female athletes - Herrington, L.; Cooke, R. (Journal of Sports Medicine and Therapy, 2017)
Background: Literature on ACL injury is limited when assessing for the presence and interaction of multiple risk factors simultaneously. Identifying risk factor interaction may increase the impact of prevention programmes to target ACL injury reduction. The aim of this study was to retrospectively assess ACL injured female athletes to identify which modifiable and non-modifiable risk factors were present at the time of injury.